Analysis Implementation of Green Accounting in Medical Waste Management at RSUD dr. Agoesdjam Ketapang - Adisty, Lyanti; Espa, Vitriyan; Damayanti, Fera (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This study aims to determine how green accounting at RSUD dr. Agoesdjam Ketapang is implemented and what barriers are faced by RSUD dr. Agoesdjam Ketapang in implementing green accounting. The application of green accounting can provide information about the extent to which an organization has a positive impact or negative impact on the environment around it. This study is qualitative research with a case study approach. Data is collected by interviewing hospital employees and analyzing existing reports and relevant documents. This study shows that dr. Agoesdjam Ketapang Hospital has implemented the concept of green accounting, but the application has yet to be carried out perfectly.  Implementing green accounting in the hospital is also considered good, with minimal obstacles in managing environmental costs. RSUD Dr. Agoesdjam Ketapang is expected to identify costs following the Hansen and Mowen environmental cost concept. This is expected to provide more detailed information related to environmental costs and become a form of corporate accountability for the environmental costs that have been spent. What distinguishes this research from previous research is the location of the research site, which is at RSUD dr. Agoesdjam Ketapang, this study discusses the obstacles to the implementation of green accounting by RSUD dr. Agoesdjam.